Edible wild plants: wild foods from dirt to plate - Kallas, John (Layton, Utah: Gibbs Smith, 2010)
Maps, explanations, photographs, and detailed descriptions offer a comprehensive overview of edible wild plants, how to identify them, and how to prepare them.
Includes reference and index
Adult
Keywords: Cook books-Wild plants-Livres de cuisine